DEVELOPMENT OF THE RIASEC 4.0 INSTRUMENT APPLICATION IN EXPLORING THE POTENTIAL, INTERESTS, AND TALENTS OF STUDENTS AT SMAN 12 LUWU TIMUR - Kartina Maming; Abdullah Sinring; Sahril Buchori (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to develop the RIASEC 4.0 instrument application for exploring the potential, interests, and talents of 11th-grade students at SMAN 12 Luwu Timur. Using a Research and Development (R&D) approach based on the Borg & Gall model, this research employs both quantitative and qualitative methods. The subjects of the study include two Counseling and Guidance experts for content validation, two Educational Technology experts for technical assessment, and students involved in three stages: initial needs assessment, validity and reliability testing of the instrument, and practicality testing of the application. Data were collected through questionnaires, expert validation sheets, observations, and interviews, and then analyzed using Pearson correlation analysis and Cronbach’s Alpha reliability. The results indicate a high demand from students for the RIASEC 4.0 application as an assessment tool for potential and interests. The application was developed with an attractive user interface design that aligns with user characteristics and achieved an average validity score of 90%. Practicality evaluations from students and guidance counselors showed average scores of 4.75 (95%) and 4.60 (92%), indicating that the application is very easy to use and effective in supporting career guidance. This research is expected to contribute to the development of technology-based career assessment instruments in schools.